PENERAPAN PEMBELAJARAN DENGAN MODEL MIND MAPPING UNTUK MENINGKATKAN KREATIVITAS DAN HASIL BELAJAR SISWA KELAS X SMA MODERN AL-RIFA’IE GONDANGLEGI KABUPATEN MALANG - Sidi Muhammad Muadz-dzin Asis Hawaya; Sugeng Hadi Utomo (Jurnal Pendidikan Ekonomi (Economic Education Journal), 2016)
To create a good learning outcomes and in accordance with the objectives then require the efforts of a teacher by looking at the pattern of student learning, mastering the lesson, choosing an appropriate learning model and not boring or monotonous and doing an effective learning process. The teacher must be careful when implementing the learning process in the classroom. Learning activity at SMA Al-Rifa'ie Gondanglegi especially in the tenth grade shows that learning is still conventional and lacking effective, then inflicting less conducive conditions and make the students become lacking enthusiastic when studying and also difficult to understand the lessons. The objectives of this research is to know that the implementation learning model of Mind Mapping can increase the creativity and learning outcomes at the tenth grade SMA Modern Al-Rifa'ie Gondanglegi. This research uses the approaching of the qualitative research, by using the Classroom Action Research (PTK). The data of the research is collected by using the observation sheets of creativity of students, documentation, note, pre-test and post-test questions and answers. The suggestion which can be given by the writer of this  research are: (1) For the teachers, they should be able to apply model of mind mapping need to consider the right subject so the learning can be done. (2) For the school, they should recall to every teachers to apply the model of learning and it is innovative and interesting. (3) For the next research, it can be given advise to apply the learning model of Mind Mapping to the other subject by replacing or adding the other variable of research.Keywords: Mind Mapping, Creativity, Learning Outcomes